2010
DOI: 10.1111/j.1365-2745.2010.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of multiple disturbances in shaping boreal forest dynamics: a spatially explicit analysis using multi‐temporal lidar data and high‐resolution imagery

Abstract: Summary1. Mixed-wood boreal forests are often considered to undergo directional succession from shadeintolerant to shade-tolerant species. It is thus expected that overstorey gaps should lead to the recruitment of shade-tolerant conifers into the canopy in all stand development stages and that the recruitment of shade-intolerant hardwoods would be minimal except in the largest gaps. 2. We analysed short-term gap dynamics over a large 6-km 2 spatial area of mixed-wood boreal forest across a gradient of stands i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 53 publications
(68 reference statements)
2
30
0
1
Order By: Relevance
“…While we have not analyzed aerial images in consecutive years, it is quite likely that the very small gaps detected here are part of repeated gap formation induced by small-scale disturbance. For example, trees of gap peripheries are more vulnerable to mortality and injury than interior canopy trees, which could lead to small openings [37]. Overall, it has been shown that repeated disturbances are important for the regeneration of species that can tolerate intermediate light levels and that are able to survive several periods of suppression from neighboring trees before growing into the canopy [38].…”
Section: Discussionmentioning
confidence: 99%
“…While we have not analyzed aerial images in consecutive years, it is quite likely that the very small gaps detected here are part of repeated gap formation induced by small-scale disturbance. For example, trees of gap peripheries are more vulnerable to mortality and injury than interior canopy trees, which could lead to small openings [37]. Overall, it has been shown that repeated disturbances are important for the regeneration of species that can tolerate intermediate light levels and that are able to survive several periods of suppression from neighboring trees before growing into the canopy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Provided that an accurate digital terrain model (DTM) exists, canopy height models, which have become popular for disturbance analysis by means of canopy gaps or canopy height profiles (Fujita et al 2003, Henbo et al 2004, Vepakomma et al 2010, could be calculated by subtracting the terrain model from the surface model , Vepakomma et al 2008. However, for our study area in the Ukraine, as well as for many other countries, accurate DTMs are lacking.…”
Section: Canopy Gap Assessment Using High-resolution Stereo Satellitementioning
confidence: 99%
“…Gap size and distribution pattern were mapped from satellite imagery by Garbarino et al [23] and Hobi et al [24]. Vepakomma [25,26] used Light Detection and Ranging (LiDAR) to assess spatial contiguity and continuity of canopy gaps over time in mixed wood boreal forests. Rugani et al [27] based a similar research question using visual stereo interpretation of scanned color-infrared (CIR) aerial photographs.…”
Section: Introductionmentioning
confidence: 99%